Structural and thermodynamic investigation of AnIVLI(O)HOPO. (8th September 2017) - Aupiais, J.; Younes, A.; Moisy, P.; Hennig, C.; Rossberg, A.; Brunel, B.; Kerbaa, M.; Vidaud, C.; Den Auwer, C.
Abstract : For the first time, capillary electrophoresis coupled with inductively coupled plasma mass spectrometry has been used to determine the stability constants of Pu IV with the multidentate hydroxypyridinonate chelating agents LI(O)HOPO in 0.1 M NaNO3 solution, pc H = 1.395 at 25 °C through competition with the NTA ligand. Abstract : For the first time, capillary electrophoresis coupled with inductively coupled plasma mass spectrometry has been used to determine the stability constants of Pu IV with the multidentate hydroxypyridinonate chelating agents 3, 4, 3-LI(1, 2-HOPO) and 5-LIO(Me-3, 2-HOPO) in 0.1 M NaNO3 solution, pc H = 1.395 at 25 °C through competition with the NTA ligand. The limiting electrophoretic mobility was found to be zero for An IV [5-LIO(Me-3, 2-HOPO)] and slightly positive for An IV [3, 4, 3-LI(1, 2-HOPO)] (An IV = Th, Pu). They were respectively assigned to the formation of the 1 : 2 neutral species An[5-LIO(Me-3, 2-HOPO)]2 and a mixture of the neutral species An IV [3, 4, 3-LI(1, 2-HOPO)] and its protonated form An IV H[3, 4, 3-LI(1, 2-HOPO)] + . The corresponding stability constants of Th IV with both chelators were evaluated through the same experiments for the sake of comparison. The stability of both Pu IV –HOPOs was about ten orders of magnitude better than that of the equivalent Th IV complexes. To complement these thermodynamic data, structural parameters of Pu[3, 4, 3-LI(1, 2-HOPO)] and Th[3, 4, 3-LI(1, 2-HOPO)] complexes in solution have been derived from EXAFS experiments and compared to previously reported crystallographic structures.